The effect of tapering on selected plasma cytokine levels following incremental training in elite male wrestlers - Karimi, M.; Heydari, H.; Eghbalian, J. (International Journal of Wrestling Science, 2011)
The aim of this study was to determine the effect of tapering on the concentration of plasma interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNFá) in elite male wrestlers after a period of incrementally increasing training volume. After completing 4 weeks of the incremental training exercise, the subjects were randomly assigned to one of two groups: a control group of wrestlers (n = 10) which continued performing the incremental weekly training volume for one week while a taper group of wrestlers (n = 10) proceeded with a 75% reduction in weekly training volume relative to the control group. Blood samples were collected from all participants at the beginning of the 1st week and at the end of the 4th and 5th weeks. Plasma levels of IL-6 and TNFá were assayed using standard commercial ELISA kits (Quantikine; R & D Systems, Minneapolis, MN). Data were analyzed by using t-test (P>0.05). The results showed that after one week of tapering, plasma levels of IL-6 significantly decreased (P>0.05). Although the plasma levels of TNFá decreased in the experimental group, it was not statistically significant (P<0.05). According to the results, increasing plasma level of IL-6 and TNFá in the wrestlers who continued incremental training might be related to the high volume of training.